High fat worsens olanzapine induced metabolic abnormalities in rats. Issue 10 (9th September 2020) - Jamaluddin, Sahara Juita; Nilugal, Kiran C.; Kulkarni, Nagaraj M.; Fattepur, Santosh; Abdullah, Ibrahim; Ugandar, Rajan Ethiraj
Abstract : Purpose: Olanzapine is widely prescribed in the treatment of schizophrenia and various psychiatric illnesses. Schizophrenia patients have been reported to eat a diet that contain higher in fat and lower in fiber. High dietary fat intake can predispose to the development of metabolic abnormalities and exacerbate hepatic changes. The aim of the paper is to investigate the effect of olanzapine and high fat diet on blood glucose, lipid profile and the liver in rats. Design/methodology/approach: Twenty-four healthy male Sprague Dawley rats were divided into following groups: group I was given normal diet, group II was given high fat diet, group III was given high fat diet and olanzapine (5 mg/kg/day intraperitoneally twice daily) and group IV was given normal diet and olanzapine (at same dose). After 30 days, the blood samples were collected to assess levels of blood glucose and total lipid profile. Also, liver specimens were processed for histological study by using light microscope. Findings: Group III showed significant increase in weight, blood glucose ( p < 0.05), total cholesterol ( p < 0.05), low-density lipoprotein-cholesterol ( p < 0.05) and decrease in high-density lipoprotein-cholesterol ( p < 0.05) when compared to group II. While group III revealed several histological changes including, dilatation and congestion of central veins and blood sinusoids as well some hepatocytes appeared damaged and were replaced by inflammatory cellular infiltrate. Originality/value: These results suggest that olanzapine and high fat diet greatly increased the blood glucose, total cholesterol, LDL-C and considerable decreased HDL-C as well as mild inflammatory changes